HOW TO INCREASE CONSUMER SATISFACTION TO GAIN CONSUMER LOYALTY: Study at Omah Wilis Caffee Shop - Adilla, Nur; Berutu, Meta Bara (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
This study aims to examine the effect of product innovation and service quality on consumer satisfaction and consumer loyalty. This study uses a quantitative approach with data collection methods through surveys. The questionnaire was distributed online using the Google Form with a total of 227 respondents. Respondents are consumers of the Omah Wilis coffee shop with a minimum age of 18 years in the last 3 months. Furthermore, the respondents' answers were processed using the Partial Least Square (PLS) application as well as through the Structural Equation Model (SEM) data analysis technique. The results showed that product innovation and service quality had a significant positive effect on consumer satisfaction and loyalty.